2004
DOI: 10.1097/01.mat.0000145052.75525.77
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Index Measurement of Native Hemodialysis Arteriovenous Fistula Feeding Artery as a Predictor for Fistula Dysfunction

Abstract: The aim of the present study was to evaluate resistive index (RI) in the feeding artery of the functioning and dysfunctioning arteriovenous fistulas (AVFs). Measurement of RI in the feeding artery using Doppler ultrasound was performed in 48 patients on hemodialysis. Twenty-seven upper arm AVFs and 21 radiocephalic AVFs were studied. The patients were categorized into three groups according to clinical function: group 1, AVFs with normal function (n = 21); group 2, AVFs with abnormal clinical function (reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…5 It has been reported that high RI values in the feeding artery were related to early AVF failure. 8 Depairon et al 9 have shown that a blood flow ratio index <4.0 and an RI >0.55 in the brachial artery indicate vascular access stenosis. A PSV >200 cm/s at the site of the anastomosis may indicate graft stenosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…5 It has been reported that high RI values in the feeding artery were related to early AVF failure. 8 Depairon et al 9 have shown that a blood flow ratio index <4.0 and an RI >0.55 in the brachial artery indicate vascular access stenosis. A PSV >200 cm/s at the site of the anastomosis may indicate graft stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…15 AVF may be complicated by aneurysm, stenosis, and thrombosis, resulting in fistula failure, 10 a major cause of morbidity in HD patients. 3 Doppler sonography has been widely used in HD patients as a noninvasive tool for the diagnosis of vascular access problems, using various parameters as flow volume of AVF, 5 RI of feeding artery, 8 RI and blood flow ratio index (QI) of brachial artery, 9 or arterial and venous PSV. 16 An AVF blood flow of at least 600-800 ml/min is considered necessary to allow sufficient removal of uremic toxins from a patient within a reasonable time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the brachial artery RI is >0.60, complication is more likely to happen. For brachial artery RI, Koseoglu et al [ 27 ] showed that brachial artery RI (measured 3–4 cm above elbow) was a predictor of AVF failure. Moreno Sanchez et al [ 19 ] reported that stenosis and thrombosis could lead to increased RI in artery inflow.…”
Section: Discussionmentioning
confidence: 99%
“…Although angiography has been considered the gold standard for imaging vascular access abnormalities, CDU may be superior in some aspects, as it provides information both on the morphology and on the function of vascular access. [3] In the literature, functional parameters of the feeding artery of native AVF have been studied, [6][7][8][9][10] but there is no study about feeding artery flow changes after balloon angioplasty of the venous stenosis.…”
Section: Introductionmentioning
confidence: 99%